Problems of Implementation of Productive Waqf in Pesantren - Siddiq, Achmad (International Conference of Moslem Society, 2018)
Discourses of Productive waqf in Indonesia has appeared since Act Number 41 Year 2004 concerning Waqf has been published. This discourse requires the management of waqf to be more productive at several institutions of waqf in Indonesia including pesantren, because all this time the management of waqf looks consumptive. this paper will discuss about what are the problems in implementation of productive waqf in Pesantren. This paper is library research. The data is taken from the book reference that explaining the pesantren experience of several pesantren such as Pesantren Gontor, Pesantren Tebuireng and Pesantren Ash-Shiddiqiyyah. The data that has been collected would be analyzed descriptively qualitative. The results of this research show that the problems of implementation of productive waqf in pesantren can be described as follows: Firstly, the majority of the positions of waqf pesantren are not yet fully owned by the public institution, so that the community is less concerned to participate in the development of waqf assets of pesantren. Secondly, The unclear status of the outcome of waqf, whether it belongs to the institution of waqf automatically or it belongs to the owner of the pesantren. Thirdly, The manager of waqf pesantren (naáº“Ã®r) is less professional. The majority of them are still patterned in the paradigm of consumptive waqf thinking, besides that the selection process of the manager of waqf perfunctorily make their sense of responsibility relatively reduced